(untitled) (Damu Journal of Sport Sciences, 2024)
The aim of the research is to build a training program based on the use of intensive centralized training to develop the strength characterized by speed and explosive power, and thus develop achievement among juniors in the National Center for the Care of Sports Talent. The researcher used the experimental method by designing the control and experimental groups and using the method of pre-post tests, as the research sample was selected from the community of young players in the National Center for the Care of Sports Talent, which had a total number of (10) players divided into two groups, a control group and an experimental group, with a number of (5) players for each group. After completing the field research procedures and processing the obtained data statistically, several conclusions were drawn, including 1-The training program prepared by the researcher had A clear positive impact on the training process of track and field juniors at the National Center for Sports Talent Care. 2-There are statistically significant differences between the pre-tests and post-tests of the control group in the research variables (the distinctive speed strength of the legs, explosive power, achievement) in favor of the post-tests.